Evaluasi Produktivitas Alat Gali-Muat dan Alat Angkut untuk Pengupasan Tanah Penutup Bulan Agustus 2016 Di Pit 3 Timur Penambangan Banko Barat PT Bukit Asam (Persero) Tbk - Muhammad Arrofah; Mardiah Mardiah; Janiar Pitulima (MINERAL, 2017)
PT Bukit Asam (Persero), Tbk is a state-owned enterprise that operates in mining industry, particularly coal mining that has 4 main mining location. One of them is an east pit 3 of Banko Barat mining managed by PT SumberMitra Jaya. Mining process is exploited by using open pit methode which excavate overburden material using load-haulage equipment and transport system. Load-haulage equipments are used excavate, and to load overburden material, and transport system are used to carry overburden in disposal. This whole processes known as mechanical mining system. However, the actual condition of load-haulage productivity was only 84.56 % compared to determined target that caused overburden remova volume not to be achieved in amount of 15.44 %. Otherwise, evaluation of factors that affected performance of load-haulage equipment and transport system need to be conducted. Evaluation was conducted by calculating productivity, work efficiency, match factor of equipment, and load–haulage geometry. The data collected was cycle time, effective utilization, kind of material overburden and load-haulage geometry to get the value. Then, the collected data processed by using formula of mechanical soil movement and analysed based on literatures that related to the problem. The causing factors of load-haulage productivity in not achievement of determined target after evaluation conducted was low of work efficiency, amount of delay time in the amount of 1.19 minute caused by narrow transport roads, and low of match factor of equitment in the amount of 0.92. The alternatives that can be carried out to increase load-haulage productivity is increasing effective work time and widing transport road. Effective work time of transport system should be leveled up from 15.237 hour to 15.682 hour in fleet I and fleet II, and in fleet III should be leveled up from 14.122 hour to 14.567 hour. Thus, the total of transport system productivity will increase to 576,503.83 bcm/month from 486,247.59 bcm/month.